سلوك التنمر لدى تلاميذ المرحلة الابتدائية وطلبة المرحلةالمتوسطة وعلاقته بالجنس والترتيب الولادي (Journal Of Educational and Psychological Researches, 2016)
The current research aims at recognize bullying for the pupils of the primary stage  and the students of the  middle stage  according to the gender variables and birth order also detection of difference significance of bullying among the variables of gender(males and females) and the birth order( the first, the second, the third, the forth, the fifth, and the sixth) and then detection of the bullying relation with these variables and to what extent each of them bullying degrees.          To achieve this objective , the researcher has chosen a sample included(480) individual of(80) individual from the fourth grade primary school pupils and (100) pupils of sixth  primary grade and (100) pupils of fifth  primary grade  and (200) pupils of first secondary  grade, and the researcher performed establishing the bullying standard composed of(24) items the answer replies by choosing one of the alternatives for (always, sometimes, no),and they are given according to the correction degrees(3,2,1) respectively thus the  Max. degree of it(72) and the mini. Degree(24)degree and the average hypothesis  (48) degrees . And the researcher has verifying of the distinctive force of its items and authentication coefficients and its steady of two methods, re-again the test and(Alfa-Cronbakh) equation and its authentication by using the correctness of the (in kind) and structure authentication.After  application of the standard over research sample and analyzing the degrees statistically the results were as follow :-The average  degrees of bullying within the research  sample and with categories variable in  gender and birth order were less than assumed  average  for standard with statistical difference  at level ( 0,05 ) .There is differences with statistical guidance at level (0,05 )in bullying between males and females for the favor of the males .There are many differences with statistical guidance  at the level (0,05 ) in bullying between birth order categories ( first , second , third , fourth , fifth and sixth ) .There is relation between bullying and each of gender and birth order , the relative contribution  of gender variable  in bullying degrees at level (0,05) equal (0.098),and for the birth order variable at level ( 0,01 ) equal (0.148). Therefore the research is concluded that the gender variable and birth order variable contribute in  bullying behavior .    Researcher recommended that the schools should undertake great importance through their activities and instruction  to get rid of bullying in the behavior of the pupils , and suggest conducting study  in the future integral to the present research .